ROLE AND PLACE OF IMPLEMENTED INNOVATIONS IN THE AGRICULTURAL SECTOR OF UKRAINE - KHAKHULA, Bohdan; HOLOVACH, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the role and place of higher education institutions in the implementation of innovations in the agricultural sector of Ukraine. Traditional farming practices have been proven to be improved and modified through automation and the introduction of modern, large-scale technological solutions that reduce risk, increase resilience and provide producers with predictive solutions to make agriculture more productive. The positive side of the transfer of knowledge is the opportunity for ZVO to get an additional way to diversify sources of income, thereby turning it into a subject of entrepreneurship in the regional economy. Implementation of innovative activity requires the presence of a system of its organization. It was called the knowledge transfer system. The most important factor in the effectiveness of knowledge transfer processes is the presence of an appropriate organizational infrastructure, which acts as an "exchange buffer" between external customers and university units, its teachers and scientists. The expansion of cooperation between subjects of the Regional Innovation System is crucial for encouraging the wide use of academic knowledge as innovations in the regional economy. Based on the concept of reviewing the role of higher education institutions as a generator of knowledge development in society, we considered the possibilities of organizing the interaction of interested parties, including business representatives and government bodies. We believe that an institute that would consolidate the scientific and technical structures of large companies, research stations and laboratories, institutions of higher education, venture investment firms, investment funds and companies, insurance companies, credit cooperatives, consulting and other specialized services, i.e. about objects that carry out various stages of the investment cycle can become an agroinvestpark. We believe that its creation will contribute to the unification of efforts in the organization of educational, research, investment and innovation activities, the improvement of the educational process of training specialists for the needs of the agricultural sector of Ukraine, the development and offering of science-intensive technologies and innovative developments on the market. Therefore, in order to promote the innovative activity of agricultural enterprises, it is necessary to develop a comprehensive and systematic personnel policy as a consistent activity of state authorities and local self-government bodies for the purpose of rational use and reproduction of the personnel potential of agriculture. We believe that for this purpose it is necessary to improve the quality of training of specialists in educational institutions of agricultural education, to reform the system of retraining and advanced training of personnel at all levels of professional education, to ensure the adjustment of training programs based on shifting the emphasis to practical training for the introduction of progressive technologies and equipment.